A new perspective on environmental controls of marine nitrogen fixation - Landolfi, Angela; Koeve, Wolfgang; Dietze, Heiner; Kähler, Paul; Oschlies, Andreas (Geophysical Research Letters, 2015)
Growing slowly, marine N2 fixers are generally expected to be competitive only where nitrogen (N) supply is low relative to that of phosphorus (P) with respect to the cellular N:P ratio (R) of non-fixing phytoplankton. This is at odds with observed high N2 fixation rates in the oligotrophic North Atlantic where the ratio of nutrients supplied to the surface is elevated in N relative to the average R (16:1). In this study, we investigate several mechanisms to solve this puzzle: iron limitation, phosphorus enhancement by preferential remineralization or stoichiometric diversity of phytoplankton, and dissolved organic phosphorus (DOP) utilization. Combining resource competition theory and a global coupled ecosystem-circulation model we find that the additional N and energy investments required for exo-enzymatic break-down of DOP gives N2 fixers a competitive advantage in oligotrophic P-starved regions. Accounting for this mechanism expands the ecological niche of N2-fixers also to regions where the nutrient supply is high in N relative to R, yielding, in our model, a pattern consistent with the observed high N2-fixation rates in the oligotrophic North Atlantic.